Konseling Sensitif Agama dan Budaya - Istiqomah, Istiqomah (Institut Agama Islam Negeri Padangsidimpuan, 2022)
Success in the continuity of the counseling process is based on the quality of the counselor both personally and also the thorough knowledge and understanding of the counselee. The counselor's self-quality consists of the counselor's psychophysical elements, while the counselee's quality of knowledge and understanding includes being sensitive or sensitive, empathetic and able to respect diversity and change so that a counselor is expected to have the ability to understand and be sensitive or sensitive to changes and individual diversity. Being sensitive or sensitive for counselors, especially in addressing cultural differences, called culturally sensitive counselors is one of the basic elements for a counselor, especially in carrying out counseling services. By being sensitive or sensitive to religious and cultural differences, the counselor will have deeper knowledge of the counselee and will provide significant benefits or it can be said as an entry point for the continuity of the counseling service process that is more effective and optimal. It is said that counseling services are more effective and optimal because being sensitive or sensitive will easily access the dynamics of religious and cultural expressions.